KEANEKARAGAMAN DAN KELIMPAHAN PERIFITON DI PERAIRAN SUNGAI DELI SUMATERA UTARA - Susanti Lawati Barus; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2014)
This research aims to know the abundance and diversity level of periphyton and to determine the pollution Deli river, in terms of periphyton diversity and water quality. Physical-chemical, and biological observed parameter that were temperature, current, brightness, pH, TDS, TSS, BOD5, DO, nitrate, Phosphate, Fe, diversity and abundance of periphyton. Sampling was done three times at the five observation station, that each station is divided into three spots (before, during and after the sewage outlet). Diversity index periphyton (H') ranged from 0,803 until 1,195 ind/cm2, abundance ranged from 257.280 until 1.185.280 ind/cm2. The temperature 27 until 30oC, the current range 0,68 until 0,89 m/s, the brightness range 20,50 until 23,50 cm, TDS range 96,50 until 142,03 mg/l TSS 5,33 until 11,33 mg/l, pH range 7,60 until 8,10 mg/l, DO 0,90 until 1,90 mg/l, BOD5 8,99 until 22,50 mg/l, nitrate 1,69 until 3,48 mg/l, Phosphate 0,11 until 0,35 mg/l and Fe 0,20 until 3,78 mg/l. According to the Diversity index (H') and water physical – chemical properties, Deli River is being heavy polluted.Keywords: Periphyton, Diversity, Abundance, Deli River